2017
DOI: 10.1177/0047237918800985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brief Intervention Workshops on Addiction Provider Knowledge, Skills, Negative Attitudes, and Interest in Implementing Evidence-Based Practices

Abstract: This study evaluated the impact of Motivational Interviewing (MI) and Screening, Brief Intervention, and Referral to Treatment (SBIRT) workshops on posttraining knowledge, skills, negative attitudes, and interest in implementing evidence-based practices (EBPs). Participants ( N = 70) were primarily mental health counselor (41.4%), social workers (20.0%), substance abuse counselors (15.7%), school counselors (5.7%), and nursing professionals (4.3%) who selected the 1- or 2-day workshop for continuing education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Many programs have been focused on youth prevention, with brief educational interventions around substance use showing positive impacts among adolescents [11]. A larger body of literature focused on adults has shown promise in the use of brief interventions for substance use treatment, and to increase knowledge of SUD among counselors and clinicians [12][13][14]. Research has also shown success in embedding adult education programs into workplaces, with limited evidence to suggest promise in promoting drug education specifically [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Many programs have been focused on youth prevention, with brief educational interventions around substance use showing positive impacts among adolescents [11]. A larger body of literature focused on adults has shown promise in the use of brief interventions for substance use treatment, and to increase knowledge of SUD among counselors and clinicians [12][13][14]. Research has also shown success in embedding adult education programs into workplaces, with limited evidence to suggest promise in promoting drug education specifically [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%